Cannabidiol as a potential treatment for psychosis - Cathy Davies; Sagnik Bhattacharyya (SAGE Publishing, 2019)
Psychotic disorders such as schizophrenia are heterogeneous and often debilitating conditions that contribute substantially to the global burden of disease. The introduction of dopamine D2 receptor antagonists in the 1950s revolutionised the treatment of psychotic disorders and they remain the mainstay of our treatment arsenal for psychosis. However, traditional antipsychotics are associated with a number of side effects and a significant proportion of patients do not achieve an adequate remission of symptoms. There is therefore a need for novel interventions, particularly those with a non-D2 antagonist mechanism of action. Cannabidiol (CBD), a non-intoxicating constituent of the cannabis plant, has emerged as a potential novel class of antipsychotic with a unique mechanism of action. In this review, we set out the prospects of CBD as a potential novel treatment for psychotic disorders. We first review the evidence from the perspective of preclinical work and human experimental and neuroimaging studies. We then synthesise the current evidence regarding the clinical efficacy of CBD in terms of positive, negative and cognitive symptoms, safety and tolerability, and potential mechanisms by which CBD may have antipsychotic effects.